The maternity ward of a teaching hospital: reconfiguration of maternal-child nursing care - Mônica Barros de Pontes; Tânia Cristina Franco Santos; Maria Angélica de Almeida Peres; Antonio José de Almeida Filho
ABSTRACT Objective: to analyze the strategies used by nurses and nurse professors for a better position in the maternity ward of the teaching hospital of the Universidade Federal do Espírito Santo. Method: this is a social-historical study with a qualitative approach. The primary sources were written documents, such as official letters, memos, ordinances, standards and routines of the hospital; photographic material; and oral testimonies from seven participants. The interviews were performed using a semi-structured questionnaire, with questions regarding the adaptation from a sanatorium to a teaching hospital, the challenges faced, and the strategies adopted by the nursing department. Results: the results allowed us to understand the close link between the maternity ward and the nursing course of the Universidade Federal do Espírito Santo, which created a differentiated nursing care that integrated training and care with a broader and humanized look. Final considerations: the actions of the nurses were recognized and gave them professional visibility, influencing a new form of care in the maternity ward.